What do Pakistani women know about New Zealand's healthcare system? - Pauline Norris; Susan Heydon; Sumera Saeed Akhtar (CSIRO Publishing, 2022)
Introduction Recently immigrated Pakistani women need knowledge about their new country's healthcare system to better access appropriate care. Aim This study explores the knowledge of Pakistani immigrant women about New Zealand's healthcare system. Methods An online questionnaire was developed and administered using Qualtrics© software. Closed and open-ended questions were asked about knowledge and challenges when entering a new healthcare system. The target population was Pakistani women aged ≥18 years, living in New Zealand for <5 years. Participants were recruited from different cities, primarily through snowball sampling using various social media. The survey was conducted in English, and responses were analysed using Microsoft Excel. Results Two hundred respondents (covering 881 family members) answered most questions. The average age of the participants was 26-34 years, and most were housewives. Recently immigrated Pakistani women considered it difficult to access information about medical centres, GP registration, subsidised medicines, maternity services, emergency/after-hours services, and mental health for children and adults. Most participants stated that they obtained information about the healthcare system from friends and searched Google. Discussion Recently immigrated Pakistani women face challenges finding information about New Zealand's healthcare system, which may impact access to health care for themselves and their families. Information is particularly needed before or soon after arrival in New Zealand.